Celebrating Al and Rose Watkins' 35th Wedding Anniversary - Watkins, Howard::::::::: (1979)
Betty Williamson, Leffie Watkins, Grace Rocco, Phil Rocco, Christine Watkins, Adam Watkins on lap of Albert Watkins